Diversity and Conservation Status of Sharks Based on Samudera Kutaraja Fishery Port, Banda Aceh - Hikmal, Zulhaikal; Salmarika, Salmarika; Imamshadiqin, Imamshadiqin; Muliari, Muliari; Rusman, Renggalyta; Farhan, Muhammad; Valentinoo, Bagas Arie Maulana (Jurnal Perikanan Terpadu, 2025)
Sharks are a group of cartilaginous fish that are vulnerable to the impacts of overfishing due to their slow growth and limited reproductive ability. Therefore, it is important to periodically collect data on shark species to update population information and identify endangered species. This study used a direct observation method with data collection based on morphological characters to identify the shark species found. Data analysis was carried out descriptively qualitatively. The results of the study recorded 44 individual sharks from various species. Chiloscyllium punctatum was recorded as the most commonly found species with 14 individuals, while Chiloscyllium hasselti was only recorded as 5 individuals. Based on conservation status, 5 shark species were found that were included in Appendix II of CITES and there were 3 non-Appendix species. These findings indicate the importance of conservation efforts to prevent future declines in shark populations